Examining the Effects of (α4)3(β2)2 Nicotinic Acetylcholine Receptor-Selective Positive Allosteric Modulator on Acute Thermal Nociception in Rats - Deba, Farah (Molecules, 2020)
Neuronal nicotinic acetylcholine receptor (nAChR)-based therapeutics are sought as a potential alternative strategy to opioids for pain management. In this study, we examine the antinociceptive effects of 3-(2-chlorophenyl)-5-(5-methyl-1-(piperidin-4-yl)-1H-pyrazol-4-yl)isoxazole (CMPI), a novel positive allosteric modulator (PAM), with preferential selectivity to the low agonist sensitivity (α4)3(β2)2 nAChR and desformylflustrabromine (dFBr), a PAM for α4-containing nAChRs. We used hot plate and tail flick tests to measure the effect of dFBr and CMPI on the latency to acute thermal nociceptive responses in rats. Intraperitoneal injection of dFBr, but not CMPI, dose-dependently increased latency in the hot plate test. In the tail flick test, the effect achieved at the highest dFBr or CMPI dose tested was only <20% of the maximum possible effects reported for nicotine and other nicotinic agonists. Moreover, the coadministration of dFBr did not enhance the antinociceptive effect of a low dose of nicotine. Our results show that the direct acute effect of dFBr is superior to that for CMPI, indicating that selectivity to (α4)3(β2)2 nAChR is not advantageous in alleviating responses to acute thermal nociceptive stimulus. However, further studies are necessary to test the suitability of (α4)3(β2)2 nAChR-selective PAMs in chronic pain models.